Handbook of environmental engineering calculations - Lee, C.C; Lin, Shun Dar (McGraw-Hill, 1999)
Solves complex problems and regulatory issues. This solutions-oriented guide takes you through the Integration of regulatory requirements into environmental design, providing tested tools that make each aspect of environmental assessment, control, protection, and compliance more manageable.